The Influence of Corporate Social Responsibility Activity toward Customer Loyalty through Improvement of Quality of Life in Urban Area - Balqiah, Tengku Ezni; Setyowardhani, Hapsari; Khairani, Khairani (The South East Asian Journal of Management, 2011)
The success of Corporate Social Responsibility (CSR) activities can create competitive advantage by influencing customer responses to firms’ offering. Customer’s awareness of CSR activity will influence their loyalty through their perception that activity can improve society’s quality of life where the CSR activities were implemented. The objective of this study is to evaluate the relationship between CSR awareness and loyalty that mediated by CSR Belief, Company Ability Belief, Quality of Life, and Company Reputation using Structural Equation Modelling (SEM). The result shows little differrences among five firms/brands as the object of the research, that are beverage, soap, car, lubricant, and cigarette. This result has an implication for the firm that CSR activities are not just cost center activities, but also can create reputation, and in the long run can create customer loyalty that contributes to firm’s financial benefit.